The Efficacy of Rituximab in the Treatment of Membranous Nephropathy - Maharjan, Ruby; Wang, Jin Wen; Shrestha, Indra Kumar (Journal of Nepal Health Research Council, 2021)
Rituximab is a chimeric monoclonal antibody directed against the CD20 expressed on B cells, originally used to treat lymphoma but is increasingly used for the treatment of autoimmune diseases. Membranous nephropathy is an autoimmune disease resulting from the deposition of IgG and complements components onto the subepithelial layer of the glomerular capillary wall and remains the leading cause of nephrotic syndrome in adults. Several prospective and retrospective studies showed rituximab induces remission and may decrease proteinuria in patients with membranous nephropathy. Considerable evidence supports the use of B-cell depletion as initial therapy in nephrotic patients with membranous nephropathy. This review focuses on the efficacy and safety of rituximab in the treatment of membranous nephropathy.Keywords: Membranous nephropathy; rituximab; treatment